Obtaining tight bounds on higher-order interferences with a 5-path interferometer - Thomas Kauten; Robert Keil; Thomas Kaufmann; Benedikt Pressl; Časlav Brukner; Gregor Weihs (New Journal of Physics, 2017)
Within the established theoretical framework of quantum mechanics, interference always occurs between pairs of paths through an interferometer. Higher order interferences with multiple constituents are excluded by Born’s rule and can only exist in generalized probabilistic theories. Thus, high-precision experiments searching for such higher order interferences are a powerful method to distinguish between quantum mechanics and more general theories. Here, we perform such a test in an optical multi-path interferometer, which avoids crucial systematic errors, has access to the entire phase space and is more stable than previous experiments. Our results are in accordance with quantum mechanics and rule out the existence of higher order interference terms in optical interferometry to an extent that is more than four orders of magnitude smaller than the expected pairwise interference, refining previous bounds by two orders of magnitude.